The dis-translation of Koran: substitute resort of translation. The matter of amr - ROSER NEBOT, Nicolás (Anaquel de Estudios Árabes, 2010)
The orientalist paradigm has been, up to the present moment, the only pattern that western society has adopted for the reception of Islam. That determines the knowledge that the West has of the Islamic ideological reality and civilisation. Furthermore, it also determines the translation of the authoritative Islamic texts, particularly the case of the Koran. In this sense, what is assumed about the orientalist ideas may lead to the not translating of those texts but to their dis-translation. In the sense that the real meaning of those original texts might be sometimes modified by the translators’ own beliefs and their lucrubrations. This can be observed in many instances with the Koranic term amr (subject or command), in the context of a study with a strong orientalist approach.